2016
DOI: 10.1002/jor.23401
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical comparison of augmented versus non-augmented sacroiliac screws in a novel hemi-pelvis test model

Abstract: Operative treatment of sacral insufficiency fractures is frequently being complicated by osteopenic bone properties. Cement augmentation of implanted sacroiliac screws may lead to superior construct stability and prevent mechanical complications. A novel hemi-pelvis test model with dissected symphysis was developed. Five fresh-frozen cadaveric pelvises were vertically osteotomized at the sacrum on both sides and fixed with sacroiliac screws in both corridors of the first sacral vertebral body. One side was ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 45 publications
(54 citation statements)
references
References 25 publications
3
50
0
1
Order By: Relevance
“…The Advantages of TiRobot Over Traditional Surgical Techniques Biomechanical studies confirmed that the stability of the anterior and posterior pelvic rings accounted for 40% and 60% [27][28][29][30] . The stability of the posterior pelvic ring is maintained by the sacroiliac joint complex, which is composed of the bilateral ilium, the sacrum, the sacroiliac joint, and the surrounding ligaments; it also plays an important role in the stability of the pelvic ring 21 .…”
Section: Discussionmentioning
confidence: 98%
“…The Advantages of TiRobot Over Traditional Surgical Techniques Biomechanical studies confirmed that the stability of the anterior and posterior pelvic rings accounted for 40% and 60% [27][28][29][30] . The stability of the posterior pelvic ring is maintained by the sacroiliac joint complex, which is composed of the bilateral ilium, the sacrum, the sacroiliac joint, and the surrounding ligaments; it also plays an important role in the stability of the pelvic ring 21 .…”
Section: Discussionmentioning
confidence: 98%
“…Placement of two iliosacral screws achieves higher biomechanical stability than just one, and, similarly, longer screws achieve a higher stability than shorter ones [86,87]. Clinically, screws often fail by loosening or unscrewing [85] due to reduced bone quality [81] which can be effectively addressed by using cannulated screws and bone cement to augment the fixation site [88,89]. Bone cement is also an option for isolated and incomplete compression fractures [83] in which the cement is injected via a needle accessing the sacrum via the sacrum ala.…”
Section: Pelvis Fracturesmentioning
confidence: 99%
“…Special care should be taken to avoid cement leakage into the sacral canal, the neuroforamina or through the anterior sacral cortex. Biomechanical studies have shown that stability of iliosacral screw fixation in FFP is significantly higher with cement augmentation than without (44,45). Clinical experience is still small, but results are promising (42,43).…”
Section: Introductionmentioning
confidence: 97%